Impact of various soil amendments on root knot nematodes and plant growth attributes of tomato (Solanum lycopersicum L.) - Tahir, Muhammad; Ali, Muhammad Amjad; Khan, Ahmad; Akram, Muhammad Zubair; Sana Ullah; Faraz, Imran; Khan, Muhammad Shahroz; Abrar, Muhammad; Ali, Fahad; Abbas, Qaisar (Journal of Pure and Applied Agriculture, 2024)
Root-knot nematodes are important plant pests that can cause significant damage to a wide range of crops, leading to yield losses and economic impact. The experiment was conducted to investigate the influence of different organic soil amendments on nematode population and plant growth attributes. The experiment was conducted using various soil amendments, including Farmyard Manure (FYM), Rock Phosphate (RP), Poultry Manure (PM), and Biochar (BC), at two concentration levels. Their effects were assessed based on various plant growth and nematode population parameters. The results indicated the highest gall population was observed in the Farmyard Manure (FYM-5%), with 24.3 galls per plant. Gall index, a measure of nematode infestation severity, showed variation among the treatments. Rock Phosphate (RP-5%) had the highest gall index of 6.4. Poultry Manure (PM-5%) exhibited the highest population, with 39.4 egg masses per plant. The Farmyard Manure (FYM-10%) treatment had the highest nematode population 120 per 250 cm3 of soil. Female populations in the soil, Poultry Manure (PM-5%) had the highest count, with 65.4 females per 250 cm3 of soil. The plant growth attributes displayed significant variations depending on the type and concentration of the soil amendment. Plant height was significantly influenced by the type of soil amendment, with the Farmyard Manure (FYM-10%) treatment resulting in the tallest plants (40.5 cm). The number of leaves per plant varied among the treatments, where Poultry Manure (both 5% and 10% concentrations) exhibiting the highest leaves (31 and 36, respectively). Root length (cm) has significant positive correlation with gall index r=0.252 and 0.955 at lower and upper limits respectively. Similarly fresh plant weight (g) had significant positive correlation with egg masses/plant r=0.976 and 0.954 at lower and upper limits respectively.